Comparison of wavelet families for texture classification by using wavelet packet entropy adaptive network based fuzzy inference system - Avci, Engin (Elsevier Science Bv, 2008)
Recently, significant of the robust texture image classification has increased. The texture image classification is used for many areas such as medicine image processing, radar image processing, etc. In this study, a new method for invariant pixel regions texture image classification is presented. Wavelet packet entropy adaptive network based fuzzy inference system (WPEANFIS) was developed for classification of the twenty 512 x 512 texture images obtained from Brodatz image album. There, sixty 32 x 32 image regions were randomly selected ( overlapping or non-overlapping) from each of these 20 images. Thirty of these image regions and other 30 of these image regions are used for training and testing processing of the WPEANFIS, respectively. In this application study, Daubechies, biorthogonal, coiflets, and symlets wavelet families were used for wavelet packet transform part of the WPEANFIS algorithm, respectively. In this way, effects to correct texture classification performance of these wavelet families were compared. Efficiency of WPEANFIS developed method was tested and a mean % 93.12 recognition success was obtained. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: texture images; expert systems; discrete wavelet packet transform; wavelet entropy; wavelet family; ANFIS